Witches, Pagans and Historians. An Extended Review of Max Dashu, Witches and Pagans: Women in European Folk Religion, 700-1000 - Hutton, Ronald (The pomegranate, 2016)
Witches, Pagans and Historians. An Extended Review of Max Dashu, Witches and Pagans: Women in European Folk Religion, 700-1000